Hardness and sliding wear characteristics of AA7075-T6 surface composites reinforced with B4C and MoS2 particles. (24th May 2019) - Patle, Hemendra; Mahendiran, P; Sunil, B Ratna; Dumpala, Ravikumar
Abstract: In the present study, AA7075-T6 based surface composites reinforced with (i) B4 C and (ii) B4 C/MoS2 particles were fabricated using friction stir processing (FSP). Microstructural characteristics of the samples were studied by using optical microscope and scanning electron microscope. It is evident from the microstructural observations that the addition of MoS2 particles improved the uniform distribution of B4 C particles in the matrix material. However, lower hardness values were observed for the surface composites compared with that of the base metal, despite the particles reinforcement. This can be explained by considering the effect of FSP on altering the amount of intermetallic phase present in AA7075. In order to improve the hardness, T6 heat treatment (solution treatment at 515 °C for 0.5 h, quenching in cold water and artificial aging at 120 °C for 24 h) was carried out for the fabricated surface composites. Sliding wear characteristics of the samples were investigated against AISI 52100 steel ball using linear reciprocating tribometer. Heat-treated (T6) FSPed composites exhibited superior wear resistance in comparision to that of the base alloy and FSPed composites.